THE EFFECT OF LISTEN-READ-DISCUSS (LRD) STRATEGY ON STUDENTS READING COMPREHENSION AT CLASS X SMA HKBP SIDORAME MEDAN - Moralina Napitupulu; Yessy Octavianna; Carolina Pakpahan (Jurnal Scientia, 2023)
The study examines how the Listen-Read-Discuss method affects students' success in reading comprehension. An experimental quantitative design was employed in this investigation. Pupils in grade X at SMA HKBP Sidorame Medan, totaling 40, made up the study's population. Each class averaged 20 pupils. The experimental group and the control group were each made up of two students. While the control group received traditional instruction, the experimental group received instruction using the Listen-Read-Discuss strategy. A multiple-choice test that was split into a pre-test and a post-test was the instrument utilized to gather the data. The t-test formula was used to assess the data. The analysis's findings indicated that the Listen-Read-Discuss strategy has a significant impact on students' reading comprehension achievement when tobserved is higher than ttable (4,65 > 2.0) at the level of significance of 0,05 and the degree of freedom (df) of 38.